Turismo e qualificação profissional: as experiências vivenciadas entre os integrantes da Associação de Condutores de Ecoturismo de Ilha Grande - Piauí/Brasil - Silva, Amanda Maria dos Santos (2014)
The current research has the purpose of investigating the effects of professional qualification courses on the labor activities of the members of Associação de Condutores de Ecoturismo de Ilha Grande (Association of Ecotourism Guides of Ilha Grande) – ILHAECOTUR – Piauí, Brazil, who sell their labor power to meet the needs of tourism market in the region of Parnaiba Delta, on its extension in Piauí state. To this end, we have taken the perspective of dialectical, historical materialism. The thread of our analysis is processed methodologically in the intertwining of written and oral sources. For this, we took a qualitative approach compounded of bibliographic and field researches, where we identified and inserted our research subjects through the Oral History. Seeking to meet the goals of this research, we collected data about the professional qualification courses attended by the members, pointing out, in our reflections, the contradictions present in this movement. We realized that, although many, the courses offered by SEBRAE and UFPI were superficial and offered a fragmented knowledge to those who were motivated to attend such courses. Despite this superficiality, this was a milestone for the organization of the workers in the sector, who point their participation as the motivator for the creation of the first local cooperative of tourism guides, the Cooperativa de Condutores e Guias de Turismo de Ilha Grande (Cooperative of Ecotourism Guides of Ilha Grande) – COOPERCIG - that had a short duration and was later disarticulated and restructured, now as ILHAECOTUR. We realized that the offering of courses, for been received passively by and articulated in absentia of the participants, helps the process of alienation and reification of workers in relation to their activity, furthermore, it has become an obstacle to greater coordination among workers acting in this sector, because there is a dispute between workers "skilled" and "unskilled", which contributes only to further exploration of both by capitalist instances which make the tourism in Parnaíba Delta their main product. Therefore, it is concluded that the effects of realization of qualification courses among members of ILHAECOTUR are mostly negative, for they provide to workers a minimum and fragmented knowledge, based on the complexity that involves tourism, generating a training focused on meeting the capitalist needs, making difficult the awareness of these workers to their importance in the development of tourism in the region they inhabit.